Call Me Call Me for Some Overtime - On Organizational Consequences of System Changes - Selander, Lisen (Lund Business Press, 2008)
Today a broad body of literature has emerged within the IS research community investigating the organizational consequences of IS implementations. However in view of these developments, it seems that practitioners are still faced with implementation problems, such as user dissatisfaction, resistance and mismatches between the new technology and existing work practices. It is this tension, within and between the managerial search for increased control and the established normative values of the employees, that constitutes the central focus of this thesis. The thesis aims at exploring organizational consequences of technological change, and Customer Relationship Management (CRM) systems in particular. Special emphasis is put on the dual relationship between the IS implementation process and the emotions, acts and behavior of those touched by it. While the empirical account of this thesis reflects the complexity of change, the final framework suggests that while a crucial part of the explanations in learning from such change rests on cognitive and normative factors, their association with work performance is not linear. It proposes that aspects such as (dis)identification, deskilling and cynicism represent an important but neglected side of CRM system implementation outcomes.
Keywords: Call Center; Organizational Change; CRM